Hacking healthcare: Navigating disconnection in the pursuit of medical care - Ems, Lindsay; Gonzales, Amy (AoIR Selected Papers of Internet Research, 2013)
In this qualitative research project we aim to understand the ways in which low-income healthcare recipients and their providers are working together to develop collaborative hacks, or solutions to problems of cell phone disconnection, to ensure continuity of care after patients leave the facility. We propose the concept "technology maintenance" to describe the issues low-income individuals face when navigating healthcare systems. These, we argue have not been taken into systematic investigation in the development of other interventionist eHealth solutions. Through conducting interviews with low-income healthcare recipients and their providers, we provide evidence of "collaborative hacks" being developed at a community clinic serving poor patients with HIV.